Recycling of Mineral Water Bottles with Chemical Foaming - Szabó, V. A.; Dogossy, G. (Acta Technica Jaurinensis, 2017)
Today, in the field of packaging technologies there is an increasing amount of one-way polymer materials. Such materials after their short lifecycle are disposed, and such pose a serious environmental impact. However, PET is a good quality technical plastic; the recycled use must be provided. In our research, we have examined the recycled material of mineral water bottles. Chemical foaming of recycled polyethylene terephthalate (rPET) was applied for quality increased reusability. Significant results were achieved in terms of mechanical properties at specific mixtures of chain extender and impact resistance enhancer, at the foaming state of the injection moulding.